Collective Bargaining and Job Benefits in Florida Municipal Police Agencies, 2000–2009 - Doerner, William M. (American journal of criminal justice, 2013)
While a recent analysis of unionization among Florida county sheriff deputies was informative, that study failed to provide a comprehensive picture of all law enforcement unionization activity in that state. More specifically, county sheriff offices account for only 20 % of all local law enforcement agencies in the state, represent approximately half the sworn personnel in Florida, and have only been engaged in collective bargaining for the past ten years. As a result, the present study incorporates municipal police agencies, a hitherto neglected portion of the Florida law enforcement community, in an effort to gain a fuller understanding of how unionization influences salaries and other job conditions. The results underscore the importance of adopting a broader orientation to understand the progression of collective bargaining objectives.